The Use of Antihypertensive and Antiplatelet Drugs on Hospital Stroke Patients - Anggy Rima Putri; Akrom Abdullah; Budiyono Budiyono (International Journal of Public Health Science (IJPHS), 2016)
Medicine is one of the most important part of the healing process, the restoration of health and prevention of disease. This study aims to describe the use of drugs, particularly antihypertensive and antiplatelet drugs in stroke patients hospitalized in PKU Muhammadiyah Hospital Bantul during December 2014-April 2015. This research is observational descriptive study. Data collection was done prospectively with a survey of stroke patients in inpatient Al-Insan and al-A'raaf wards in PKU Muhammadiyah Hospital Bantul during the specified period. During the study there were 61 stroke patients sampled in the study, of which 41 (67.2%) were geriatrics and 20 (32.8%) were not geriatrc. From the data, 28 (45.9%) patients did not receive antihypertensive drugs, only 33 (54,1%) patients received antihypertensive drug.The antihypertensive drugs type were given to patients were ACEI 9 (14.8%) and CCB 6 (9.8%), as well as combinations ACEI and CCB 7 (11.5%). Most patients did not receive antiplatelet 43 (70.5%), whereas patients receiving antiplatelet drugs most was the kind of aspirin 17 (27.9%). From the above data it can be concluded that the use of antihypertensive drugs in stroke patients in the inpatient ward in PKU Muhamaddiyah Hospital Bantul quite frequently used, while the use of antiplatelet drugs in these cases rarely used.